2012
DOI: 10.1002/hbm.22163
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory and inhibitory mechanisms underlying somatosensory habituation

Abstract: Habituation is a basic process of learning in which repeated exposure to a sensory stimulus leads to a decrease in the strength of neuronal activations and behavioral responses. In addition to increases in neuronal activity, sensory stimuli can also lead to decreases in neuronal activity. Until now, the effects of habituation on stimulus-induced neuronal deactivations have not been investigated. We performed functional magnetic resonance imaging in 30 healthy subjects during repetitive unilateral somatosensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
0
19
1
Order By: Relevance
“…This finding was interpreted to be based on an attenuation effect of underlying neural activity. However, studies using an event-related stimulus design have also found differences between the shapes produced by the PBR and NBR (Klingner et al, 2011b(Klingner et al, , 2014, which could not be explained by neuronal attenuation.…”
Section: Origin Of the Nbrmentioning
confidence: 88%
See 3 more Smart Citations
“…This finding was interpreted to be based on an attenuation effect of underlying neural activity. However, studies using an event-related stimulus design have also found differences between the shapes produced by the PBR and NBR (Klingner et al, 2011b(Klingner et al, , 2014, which could not be explained by neuronal attenuation.…”
Section: Origin Of the Nbrmentioning
confidence: 88%
“…This demonstrates that repetitive exposure to a stimulus can change an initially positive BOLD response into a negative response (below baseline) by decreasing the absolute amplitude of the response (Klingner et al, 2014). It has been suggested that NBRs originate from a general change in the balance between excitatory and inhibitory effects, although the net result generally favors inhibition (Klingner et al, 2014). This hypothesis is in agreement with animal experiments that have demonstrated that both excitation and inhibition take place in regions experiencing an NBR at the level of the cortical columns (Devor et al, 2005(Devor et al, , 2007.…”
Section: Nbr In the Si And Their Functional Importancementioning
confidence: 94%
See 2 more Smart Citations
“…The induction of negative BOLD in the somatosensory cortex ipsilateral to a peripheral stimulus correlates with a reduction in perceptual sensitivity of the non-stimulated hand (Kastrup et al, 2008), reflecting neuronal hyperpolarization and increased inhibition (Devor et al, 2007). The physiological importance of such mechanisms is supported by their involvement in somatosensory habituation (Klingner et al, 2012) and implication in the enhancement of contrast between stimulated regions of visual cortex and surrounding regions with adjacent receptive fields (Wade and Rowland, 2010). In the latter case, active long-range suppressive mechanisms have been invoked to explain the emergence of negative BOLD signals.…”
Section: Discussionmentioning
confidence: 99%